Aplicación de tecnología blockchain para la trazabilidad de muestras de laboratorio - Irigoyen Villacorta, María del Carmen (2020)
In times where digital transformation takes center stage to respond to the new needs and habits acquired by society, disruptive business models arise for guarantee to the end user the inalterability, transparency and security of their data and transactions carried out. Blockchain technology is born to make these business more secure and transparent by creating a perfect audit trail for each user. This technology has been used successfully in other business areas and its replication in health sector would be a great impact due to the type of sensitive information it manages. We find, in this sector, a need to be solved in the area of clinical and anatomic pathology due to the loss of patients clinical tests, which generates delay in diagnosis and timely treatment. This project proposes the development of “BlockSalud”, a system that allows the registration and traceability of the patients clinical tests from extraction to processing and makes all the associated information available at each stage of the process by the use of QR labels attached to the containers. Also, identifies the user responsible for the transfer and handling of these by geolocation. To execute this project is required an initial investment of S/. 296,543.28. The recovery is generated from the third year. It has an economic and financial net present value (NPV) of S/. 437,193.99 and S/. 225,228.35 respectively. This disruptive business idea is scalable to other health areas or business and is sustainable over the time because it covers the transparency and inalterability requirements of the current business world demands. Key words: blockchain, traceability, inalterability, lab tests, disruptive technology.